A Taxonomic Review of the genus Megaulacobothrus Caudell, 1921 (Orthoptera: Acrididae: Gomphocerinae) from South Korea - Kim, Tae-Woo (Zootaxa, 2008)
The genus Megaulacobothrus Caudell, 1921 is reviewed from South and North Korea. As a result, Megaulacobothrus aethalinus (Zubovski, 1899) is reconfirmed, Megaulacobothrus latipennis (Bolívar, 1898) is established as a doubtful species within the Korean fauna, and Megaulacobothrus jejuensis sp. nov. is newly described from Jeju Island, South Korea.